O crime de relação sexual ilícita (zinà) do direito islâmico:uma análise dos direitos humanos da mulher muçulmana - Freitas, Larissa Tavares de (2022)
This dissertation dwells on the crime of unlawful sexual intercourse, or zinà, from the Islamic Criminal Law, an offense which criminalizes any sexual relation, consensual or not, which does not fall within the established legal framework which allows this act, namely: marriage, the semblance of marriage or ownership of a female slave. The misdeed in question, which is appointed in the Qur’an and the Sunnah, the two main sources of this religious legal system, can be subdivided in two species: fornication, for non-married persons, and adultery, for extramarital sexual relations. The penalties for each of these illicit acts are, respectively, 100 lashes and death by stoning. The criminalization of sexuality found in the situation studied disproportionately affects Muslim women, despite divine guidelines not distinguishing between genders, and, in light of that, the present research aims to determine whether it is possible to overcome the criminalization of illicit sexual intercourses through an intercultural dialogue between International Human Rights Law and Muslim Law. To this end, the first chapter is dedicated to understanding how this religious legal system is internally organized, the origin of this crime and the role played by Muslim women in the umma, or Muslim community. The second chapter, in turn, is dedicated to making a theoretical outline of the definitions of fundamentalist theologies, to analyzing the criminalization of adultery in other religious strands, and to understanding how female sexuality is controlled both throughout the formation of criminological thinking and within two fundamentalist and traditionalist theologies: Islamic fundamentalism and Christian fundamentalism. The third chapter, lastly, analyses the areas of conflict between International Human Rights Law and Shari'a, reports occurrences of zina in contemporary times, both through doctrine and documents from non-governmental organizations, with special attention to the reality of Pakistan, and, finally, lists possible reforms to the criminalization of illicit sexual intercourse. This is a qualitative research whose theoretical place is interdisciplinary. Regarding its goals, it is exploratory, and explanatory, developed through the review of literature and the documental analysis of regional and global International Human Rights charters and Islamic legal sources. By the end of the study, it is concluded that, theoretically, overcoming the criminalization of zinà is possible, but not feasible, given the status of divine law associated with its origin and the fundamentally patriarchal structure upon which classical fiqh was based at the time of the consolidation of Islamic legal thinking. However, intra-religious alternatives for the reinterpretation of penalties and evidence supporting this crime, especially those offered by pluralist and progressive theologies, among which Islamic feminism stands out, prove to be effective in promoting the Human Rights of Muslim women and in protecting their sexual autonomy, if effectively implemented.